Barriers and enablers to the engagement of junior doctors in quality improvement. (24th May 2012) - Jamil, F; Foley, T; Bate, A; Tse, Y; Moghal, N
Abstract : Aim: Paediatric junior doctors have the potential to identify inefficiency and poor quality care in the systems they work in. Some engage with influencing and affecting system change, but many do not. What are the barriers to and enablers of quality improvement engagement of junior doctors? Methods: We delivered a questionnaire to junior doctors in the North East paediatric deanery. The qualitative and quantitative results were triangulated to identify the barriers and enablers to engagement that are most important to junior doctors. Results: 28 trainees (ST1-8) completed the questionnaire. All the junior doctors had encountered system problems and felt that they had a role in improving services; two thirds identified system problems at least weekly or daily; 61.5% had made suggestions or engaged in trying to improve the work in their environments. The key motivators that would encourage junior doctors to suggest, initiate or lead change were; an increased awareness of the true cost of resources; understanding the consequences of not improving the quality of the service; recognition of quality improvement efforts in appraisals, portfolios and career progression. 88% wanted training in how to achieve change. Over two-thirds of the junior doctors concluded that audit had not been a good use of their time nor contributed to any improvement. The following were considered barriers to change (based on majority score): Limited knowledge of quality improvement methods; Differing definitions of high quality care; Belief that such initiatives never work and are a waste; Don't feel part of the organisation; Senior clinicians not valuing the views of juniors; Conflicting views on who is responsible for change; Lack of time; Lack of resources; A history of failed initiatives; Potential negative effects elsewhere in the system; Lack of practical examples of benefit; Lack of quick delivery on benefits; Poor training in change management; Unfamiliarity with management; Distrust of management; Problems with group dynamics; Conclusions: Junior doctors are a motivated but untapped resource to affect quality improvement. The barriers identified can be overcome by deaneries and employers recognising the need to building quality improvement capability through training and application of proven Qi methods.